Analysis of Hybrid Power Plant Technology Using Data Weather in North Sumatera - ., Rimbawati; Azis Hutasuhut, Abdul; Chaniago, Yusniati (International Journal of Engineering and Technology, 2018)
North Sumatera which has areas of extreme enough 0-350 altitude above sea stretching from the coast of the Strait of Malaka to the Bukit Barisan mountains, resulting in some very isolated areas and may not be covered by the electricity supply ongride. It is very necessary to conduct basic research on the application of hybrid power generation technologies to meet the lighting facilities in remote villages. After surveying potential at three points, namely: the lowlands, plains and plateaus. From the data analysis shows that, forLowland rainfall amounts average of 166 mm/month, solar irradiance an average of 185.78 Wh/m2/day and an average wind speed of 2.68 knots. Furthermore, to the plains of moderate rainfall average of 176 mm/month, the intensity of solar irradiance 176 Wh/m2/day and wind speeds average 2,32 Knot, while the highlands rainfall average ranges from 171 mm/month, the intensity of solar irradiance 181.09 Wh/m2/day as well as wind speed 2.5 knots. This shows North Sumatera province is potential to develop a hybrid power generation technologies (microhydro, solar, wind and battery) to support the accelerated development of the villages.Â Â Â